Aplicaciones de un acelerómetro para la medición de inclinaciones horizontales y verticales utilizando microcontroladores avanzados y comunicación serial datalogger e interfaz gráfica. fuente de energía 4 pilas recargables - Quizhpe, Nelson (2010)
The module presented in this project is about a sensor that mesuares the slope of an object. This is a parallax mechanism that is very usefull and has many aplications. The MX2125 sensor works without any external influence. This mechanism composed of a square receptacle with an calorific element warms up a bubblle of gas detected by 4 temperatures sensors. Wich changes their temperature depending on how near they are from the gas bubble. We chose this project because it is very interesting to find aplications and show that theire devices can be controlled with microcontrolers in different programming languages. In our case Mikrobasic Pro. We had to use two microcontrollers because and four CCP modules, two per each one. The outputs of the sensor are pwn signals. For this reason we made a program that mesures the width of the pulse using two interruptions, one for the upgoing transition and another one for the downgoing one. The implementation wasn't too complicated we just had to take care of the recomendations from the manufacturer and comply with the safety rules to avoid damages in our project.